The impact of psychosocial classroom learning environment towards higher order thinking skills ability of secondary school students in accounting studies - Jamaluddin, Nor Sa'adah; Abdul Kadir, Suhaida; Abdullah, Arnida; Alias, Siti Noormi (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
The aim of this study is to investigate secondary school students’ perceptions of their psychosocial learning environment in Accounting Studies, and whether their perceptions were related to their Higher Order Thinking Skills (HOTS) ability. A convenience sample of Secondary Four students (N = 352) studying Accounting Studies in Peninsular Malaysia participated in this research by completing a self-administered questionnaire which included the Inventory of Students' Perceived Learning Environment (ISPLE) and Higher Order Thinking Skills Test and demographic information on zone in Peninsular Malaysia. This study tries to explore the students’ perception of their psychosocial learning environment, based on four dimensions, which include Learning Facilities, Constructivist-Oriented Teaching, Clear Goals and Coherence of Curricula, Student Autonomy, and Student-Student Cooperation. This study also focuses on the students’ perceptions of their psychosocial learning environment in Accounting Studies between zones in Peninsular Malaysia. Data was analysed using SPSS version 21.0 in the form of mean, standard deviation and multiple regression. Analysis of the findings of this study were presented using descriptive and inferential statistics. Multiple regression analyses indicated that two of the five scales of ISLPE were predictors of higher order thinking skills ability. Clear Goals and Coherence of Curricula was the strongest predictor and was positively associated with higher order thinking skills ability and Learning Facilities was also positively related to higher order thinking skills ability. The findings of the study are also discussed with reference to developing students’ higher order thinking skills ability in Accounting Studies classrooms.